2020
DOI: 10.1017/qua.2020.32
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on the last deglaciation of the Cordilleran Ice Sheet in coastal Southeast Alaska

Abstract: Understanding marine-terminating ice sheet response to past climate transitions provides valuable long-term context for observations of modern ice sheet change. Here, we reconstruct the last deglaciation of marine-terminating Cordilleran Ice Sheet (CIS) margins in Southeast Alaska and explore potential forcings of western CIS retreat. We combine 27 new cosmogenic 10Be exposure ages, 13 recently published 10Be ages, and 25 new 14C ages from raised marine sediments to constrain CIS recession. Retreat from the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 64 publications
(139 reference statements)
4
77
0
Order By: Relevance
“…This date is approximately a thousand years older than current estimates [ 11 , 61 ]. While the continental, interior route between the two North American ice sheets only became biologically viable after approximately 13 000 years BP [ 17 , 18 ], the Cordilleran Ice Sheet likely rapidly retreated along the NPC, creating an ecologically viable corridor around southeast Alaska beginning at least 17 000 years ago [ 20 , 62 ], with the inner fjords and sounds ice-free by 15 000 years ago [ 22 ]. Archaeological [ 7 ] and genetic [ 3 , 4 ] evidence supports the hypothesis that the first humans migrating into the Americas used a coastal route instead of the continental route [ 5 , 18 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This date is approximately a thousand years older than current estimates [ 11 , 61 ]. While the continental, interior route between the two North American ice sheets only became biologically viable after approximately 13 000 years BP [ 17 , 18 ], the Cordilleran Ice Sheet likely rapidly retreated along the NPC, creating an ecologically viable corridor around southeast Alaska beginning at least 17 000 years ago [ 20 , 62 ], with the inner fjords and sounds ice-free by 15 000 years ago [ 22 ]. Archaeological [ 7 ] and genetic [ 3 , 4 ] evidence supports the hypothesis that the first humans migrating into the Americas used a coastal route instead of the continental route [ 5 , 18 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that the retreat of the Cordilleran Ice Sheet along the Northwest Pacific coast (NPC), combined with ocean levels lower than today, provided an earlier, ice-free coastal corridor for early humans and other biota [ 20 , 21 ]. Islands along the NPC, including the Alexander Archipelago in southeast Alaska, held a unique biotic diversity and were resource-viable by approximately 17 000 ago, when the Cordilleran Ice Sheet started to retreat at its westernmost edge [ 20 , 22 ]. This timing is roughly contemporaneous with the genetic evidence for the first human migration wave into the New World [ 5 , 15 , 18 , 20 ], and consistent with genetic data that suggest dogs had already been domesticated.…”
Section: Introductionmentioning
confidence: 99%
“…Bathymetry (Carrara et al, 2003(Carrara et al, , 2007 and palynology (Ager, 2019;Barrie et al, 1993;Mann & Hamilton, 1995) support the persistence of refugia of varying complexities. Cosmogenic exposure dating has shed recent doubt on hypothesized refugial locations (Lesnek et al, 2018(Lesnek et al, , 2020, although many small refugia may remain unsampled, potentially located further west on the continental shelf only exposed during lower sea levels. Consistent signatures of refugial persistence across taxa (Colella, Lan, et al, 2018;Foster, 1965;Heaton et al, 1996;Hewitt, 2000Hewitt, , 2003Sawyer et al, 2019;Slager et al, 2020;Weckworth et al, 2005), now including martens, and the rapid colonization of previously glaciated regions following glacial recession support the persistence of complex and taxonomically diverse refugial communities along the coast during the LGM and perhaps earlier glacial advances.…”
Section: Coastal Paleoenvironmentsmentioning
confidence: 99%
“…A minimum ice thickness of 400 m is suggested for some shelf areas (Josenhans et al, 1995;Barrie and Conway, 1999), and an ~690 m thickness is suggested in the northern Hecate Strait and Dixon Entrance . Off southeastern Alaska, ice is considered to have reached the shelf break, particularly down the sea valleys such as Chatham Strait, though many areas off the Alexander Archipelago (Prince of Wales and Baranof Islands) are considered to never been Research Paper glaciated, similar to Haida Gwaii (Kaufman and Manley, 2004;Carrara et al, 2007;Lesnek et al, 2018Lesnek et al, , 2020Brothers et al, 2020). Glaciation reached its maximum extent sometime after 23.0 ka (Blaise et al, 1990).…”
Section: Glacial Historymentioning
confidence: 99%
“…Ice had largely left the lowlands and offshore region by 14.5-13.0 ka (Barrie and Conway, 1999;. Off southeast Alaska, the initial retreat of marine-terminating ice margins from their maximum extent was driven by factors acting on the ice-ocean interface, including sea-level rise and ocean warming, leading to intense ice loss via calving in the early stages of deglaciation (Lesnek et al, 2018(Lesnek et al, , 2020.…”
Section: Glacial Historymentioning
confidence: 99%